Coalescing Aid Influences on Acrylic Latexes Property and Film Formation Process. (26th December 2016) - Yi, Wang; Zhonghua, Chen; Fei, Yu
Abstract : The coalescing aid of propylene glycol phenyl ether (PPh) influences on the latexes system and its film formation process have been demonstrated in this paper. The latexes with differentT g are synthesized by seeded semicontinuous emulsion polymerization. The PPh have a significant impact on the water evaporation stage, in which PPh decreased the water evaporation rate for a lowT g latex system but accelerated the rate for a highT g latex. This result was quantified using Routh-Russel model which was a useful model for the prediction of the latex particle deformation mechanisms. The different amounts of PPh can change the latex particle deformation mechanisms. The TGA results show that the PPh still exist in the latexes films during drying. The microstructures of the latex film which dry under 70°C with the PPh for different time display that the PPh can accelerate the polymer molecules motion and the diffusion rate for the latex coalescence stage.